Shear strengthening of RC beams by means of NSM FRP strips : constitutive law of a single strip - Bianco, V. (2010)
The need to provide a rational explanation to the observed peculiar failure mode affecting the behaviour, at ultimate, of a Reinforced Concrete (RC) beam strengthened in shear by Near Surface Mounted (NSM) Fibre Reinforced Polymer (FRP) strips, led the authors to develop a comprehensive numerical model for simulating the NSM shear strength contribution to RC beams throughout the entire loading process as function of the Critical Diagonal Crack (CDC) opening angle. That model was respectful of equilibrium, ki-nematic compatibility and constitutive laws. Despite its high level of prediction accuracy, taking into account all of the possible failure modes, as well as the interaction among adjacent strips, that model resulted rela-tively complex to be easily implemented in a practitioners-addressed building regulations code. Yet, it can be conveniently simplified into a more user-friendly and closed-form design formula. Crucial point of that sim-plification is the development of a reliable constitutive analytical law providing the single strip strength as function of the imposed end slip. This paper presents the modelling strategy adopted to determine that consti-tutive law, as well as its final analytical expression.